2021
DOI: 10.3390/en14112995
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Strength and Elastic Properties of Lower Paleozoic Shales from the Baltic Basin, Poland

Abstract: The paper presents the results of laboratory studies on the strength–strain properties of shales representing four siltstone-claystone lithostratigraphic units occurring in the Baltic Basin. Laboratory studies in a triaxial stress state were conducted as single failure tests on cylindrical samples oriented parallel and perpendicular to lamination within the rocks. Mutually perpendicular samples were cut out from the same drill core sections in order to determine mechanical anisotropy. Samples oriented parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The Sasino Shales are more siliceous, with an average to 45% clay minerals, 52% QFP, and only 3.5% carbonates. As indicated in [32], the mechanical and deformation properties of rocks from different units differ significantly. The results of the performed XRD analyses and petrophysical properties of the analyzed rocks were presented in detail in [32][33][34].…”
Section: Characteristics Of the Materialsmentioning
confidence: 99%
“…The Sasino Shales are more siliceous, with an average to 45% clay minerals, 52% QFP, and only 3.5% carbonates. As indicated in [32], the mechanical and deformation properties of rocks from different units differ significantly. The results of the performed XRD analyses and petrophysical properties of the analyzed rocks were presented in detail in [32][33][34].…”
Section: Characteristics Of the Materialsmentioning
confidence: 99%
“…Mayr et al [24] proposed the porosity deformation approach (PDA) to the elastic anisotropy of shale under triaxial loading and found that the velocity change due to hydrostatic loading can be used to predict elastic anisotropy under additional axial loading. Wilczynski et al [25] studied the anisotropy of strength and elastic properties of lower Paleozoic shales from the Baltic basin, Poland, and found that the shale was characterized by VTI type (vertical transverse isotropy) internal anisotropy. Xu et al [26] adopted a finite-element-based continuum damage mechanics model to capture sample size effects and the influence of intrinsic anisotropy on the stressstrain response of shale and investigated deformation and stiffness anisotropy induced by damage propagation in a rock brittle deformation regime.…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter within the rock matrix directly controls organic porosity and adsorbed gas [2,13,14]. Additionally, TOC affects mechanical anisotropy (Sone and Zoback, 2013a), geomechanical properties [15][16][17][18][19], and brittleness [3,4,20]. In the global perspective, better gross estimation of shale reservoir requires the importance of a more precisely defined TOC model for future development activity.…”
Section: Introductionmentioning
confidence: 99%